Computational fluid dynamics simulation of the effect of drill pipe rotation on cuttings transport in horizontal wellbores using a Newtonian fluid - Ofei, T.N. (Institution of Engineering and Technology, 2015)
This project aims to numerically analyze the effect of drill pipe rotation on cuttings transportation in horizontal wellbores. For this purpose, Computational Fluid Dynamic (CFD) ANSYS 15.0 CFX was utilized to model the design at various pipe rotation speeds, fluid velocities, and a constant rate of penetration (ROP) of 60 ft/hr. The performance of the proposed model was compared with an experimental benchmark study conducted by Osgouei 2010. The model setup was validated by comparing both simulated pressure losses and cuttings concentrationsat0 rpm and 60 rpm. The outcomes showedan excellent agreement for both calculated and experimental results. Simulated pressure loss values deviated slightly from the experimental data with a mean percentage error of 2.18 % and 4.40 %for 0 rpm and 60 rpm respectively. Similarly, the calculated cuttings concentration value exceeded the experimental results with a mean percentage error of 6.40 % and 11.82 %for 0 rpm and 60 rpm respectively. The obtained results showed that increasing drill pipe rotation from 0 rpm to 120 rpm significantly reduced the cuttings concentration by 84.3% in the annulus with slight incremental pressure losses by 1.8% at 2.4384 m/s (8 ft/s). However, at high fluid velocity, drill pipe rotation effect is minimal. It also showed that for a stationary drillpipe (0 rpm), increasing the fluid velocity from 1.524 m/s (5 ft/s) to 2.4384 m/s(8 ft/s) caused a significant incremental annular pressure loss by 52.6% and a dramatic decrease in the cuttings concentration by 109.4%. Furthermore, with a constant mud properties, observed flow patterns showed a transition from a stationary bed into a moving bed and a dispersed flow when increasing drilling mud velocity and drill pipe rotation. The use of this computer simulation approach eliminates the need for much more expensive laboratory set-ups and can be used to study an unlimited number of physical and operational conditions.